Are Intertidal Mudfl at Communities (Fish And Shrimp) Affected by Cockle Culture? - Lee, Soon-Loong; Chong, Ving-Ching; Loh, Kar-Hoe; Yurimoto, Tatsuya (Malaysian Journal of Science, 2013)
Extensive cockle culture on coastal intertidal mudfl ats which function as productive feeding grounds for fi sh and shrimp may affect mudfl at productivity and disturb feeding activity. The aim of the present study is to examine fi sh ingressions into two adjacent coastal mudfl at areas, one with cockle culture and the other without cockle culture, especially to compare their diversity and abundance. Two sampling sites were selected at Bagan Sungai Buloh (BSB: with cockle bed) and BaganPasir (BP: without cockle bed) in the Kuala Selangor mudfl at area. Monthly samplings were carried out on spring tide using an enclosure trap (belat lengkung). In six months of samplings, 63 identifi ed species of fi shes and eight species of prawns were recorded. Both mudfl ats differed in their fi sh species richness, with 59 species in BSB and 41 species in BP. However, the BP m udfl at had signifi cantly higher fi sh biomass (142.2 Â±148.7 kg/ha) than BSB mudfl at (43.6 Â±41.2 kg/ha) (t-test, p<0.05). As for mean fi sh abundance, the difference between two sites is not signifi cant. Most frequent fi sh species that regularly occurred every month on both sites were the grey mullet Liza subviridis and tongue sole Cynoglossus bilineatus. There was no signifi cant difference in penaeid shrimp abundance and biomass between both sites. The dominant species of shrimps in term of biomass in BSB was Fenneropenaeus merguiensis, whilefor BP was Metapenaeus affi nis. Low abundance and biomass of fi sh species in cockle culture area are likely due to direct disturbance from culture activity as well as continually scoured sediments from cockle harvests which may affect mudfl at productivity. (Keywords: Mudfl at, cockle culture impacts, faunal abundance and biomass